Compressive behavior of lightweight concrete using aerogel-reinforced expanded polystyrene foams. (December 2022) - Jiang, Tao; Wang, Ying; Shi, Shanshan; Yuan, Nan; Ma, Rong; Wu, Xinfeng; Shi, Danda; Sun, Kai; Zhao, Yuantao; Li, Wenge; Yu, Jinhong
Abstract: The continuous development of the construction industry is also pushing concrete to change. Lightweight and high-strength concrete is becoming more and more important. Aerogel reinforced Epoxy Macrospheres (AR-EMS) were obtained by the ball rolling method. The lightweight concrete was prepared by mixing AR-EMS, cement, and hollow glass beads into the mold by the molding method. In this experiment, the influencing factors such as stacking volume fraction, inner diameter, wall thickness of AR-EMS and different types of hollow glass microspheres (HGMS), different content and length of glass fibers (GF) in matrix were studied. The comprehensive microstructure and performance characterization results show that AR-EMS binds well to the concrete matrix, and the addition of long fibers effectively improves the compressive strength of lightweight concrete. The lightweight concrete can meet the requirements of both high strength (11.46 MPa) and low density (0.897 g/cm³) when the matrix is filled with 2 wt% of 12 mm GF and AR-EMS with 9–10 mm-2layers-90%. Compared to the concrete without GF and the EPS-filled concrete, the maximum compressive strength was increased by 69% and 398%, respectively.